IMPLIKASI INVENTORY COSTING TERHADAP PERHITUNGAN LABA DAN BEBAN PAJAK DI SEKTOR PERDAGANGAN - Christina, Silvy; Tjhai, Fung Jin (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2026)
Business competition in the trading sector requires entrepreneurs to have a solid understanding of accounting aspects, particularly in inventory management. Inventory is one of the most important assets, as it directly affects the determination of the cost of goods sold, profit, and tax expenses borne by the company. In practice, trading business practitioners often face difficulties in understanding the implications of choosing different inventory valuation methods, such as First In First Out (FIFO) or the Average Cost Method. In response to this issue, Trisakti School of Management organized a training program aimed at helping students understand cost calculation methods and their tax implications. The activity was conducted on August 9, 2025, and was enthusiastically attended by 41 students. The training consisted of a combination of theoretical sessions, practical exercises, and evaluations through post-tests and questionnaires. The post-event questionnaire results indicated that the training effectively enhanced students’ understanding of the material, as reflected in the high evaluation scores given by the participants. This training is expected to be conducted regularly to deepen students’ knowledge of inventory accounting and taxation from an early stage, thereby equipping them with essential skills for their future careers.